(untitled) (PUBMET, 2025)
Introduction: Bibliometric analyses have become fairly frequent in today’s science (Donthu et al., 2021; Klarin, 2024; Öztürk et al., 2024). They help map out research areas and evaluate the quality of scientific research. Most bibliometric analyses today gather their data from Web of Science or Scopus. Yet, the methodology sections on obtaining that data often leave us wanting, especially in the few cases where datasets from both databases were merged (Echchakoui, 2020). The aim of our research was to create a comprehensive database of all publications by Croatian clinicians, regardless of the research area, so we could map their areas of interest during the period 2005-2022, as well as study potential effects of Croatia’s European Union (EU) membership. Our focus on publications by clinicians rather than publications in clinical medicine led us to create a more complex data retrieval strategy, using affiliations instead of research areas.